Public Relations Strategy Of Sidomulyo Village Government In Maintaining A Positive Image In Sibiru-Biru District, Deli Serdang Regency - Rendi Ramadhan; Muhammad Alfikri Matondang (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2026)
This study aims to determine the Public Relations strategies employed by the Sidomulyo Village Government to maintain a positive image in Sibiru-Biru District, Deli Serdang Regency. This study employed qualitative methods with a descriptive approach. Eight informants were selected using purposive sampling. These included the Village Head, Village Secretary, BPD Chair, community leaders, village residents, and Karang Taruna (Youth Organization) administrators. Data collection involved observation, in-depth interviews, and documentation. Data analysis involved data reduction, data presentation, and conclusion drawing. The results indicate that the Sidomulyo Village Government implements various Public Relations strategies through two-way communication with the community, holding village meetings, information transparency, utilizing social media as a means of public communication, and providing responsive public services. These strategies have been effective in increasing public trust in the village government, thereby maintaining its positive image. Supporting factors for these strategies include communicative leadership, support from community organizations, transparent budget management, and community participation. Inhibiting factors include limited human resources, low digital literacy among some residents, and unequal community participation.